2016
DOI: 10.1021/acsmedchemlett.6b00328
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent and Selective Leads against Toxoplasma gondii Dihydrofolate Reductase via Structure-Based Design

Abstract: Current treatment of toxoplasmosis targets the parasite's folate metabolism through inhibition of dihydrofolate reductase (DHFR). The most widely used DHFR antagonist, pyrimethamine, was introduced over 60 years ago and is associated with toxicity that can be largely attributed to a similar affinity for parasite and human DHFR. Computational analysis of biochemical differences between Toxoplasma gondii and human DHFR enabled the design of inhibitors with both improved potency and selectivity. The approach desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 25 publications
1
26
0
1
Order By: Relevance
“…Recently, researchers reported that computational analysis of biochemical differences between human and T. gondii dihydrofolate reductase enabled the design of inhibitors with both improved potency and selectivity against T. gondii (Welsch et al, 2016). El-Zawawy et al reported that incorporating triclosan into in the lipid bilayer of liposomes allowed its use in lower doses, which in turn, reduced its biochemical adverse effects (El-Zawawy et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, researchers reported that computational analysis of biochemical differences between human and T. gondii dihydrofolate reductase enabled the design of inhibitors with both improved potency and selectivity against T. gondii (Welsch et al, 2016). El-Zawawy et al reported that incorporating triclosan into in the lipid bilayer of liposomes allowed its use in lower doses, which in turn, reduced its biochemical adverse effects (El-Zawawy et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…As T. gondii is incapable of salvaging thymidine from the host, DHFR inhibition leads to indirect inhibition of TS, but the direct inhibition of TS would logically be preferred . Differences in amino acid sequences and structures of human and T. gondii DHFR have paved the way for the selective inhibition of these enzymes, whereas the considerable homology between TS of the parasite and human makes the design of selective inhibitors of the TS difficult . Antibiotic resistance is also a challenging and growing public health problem, threatening the effective prevention and treatment of infections .…”
Section: Introductionmentioning
confidence: 99%
“…T. gondii is an obligate cosmopolitan apicomplexan intracellular parasite which affects more than one‐third of the world population . Infection by T. gondii causes the worldwide disease toxoplasmosis .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the parasite creates a wide spectrum of disease, especially in congenital toxoplasmosis that causes serious fetal malformation during pregnancy . Acute toxoplasmosis can also be seen in immunocompromised patients . T. gondii utilizes a bifunctional form of the fusion enzyme dihydrofolate reductase‐thymidylate synthase (DHFR‐TS) for folate metabolism and pyrimidine biosynthesis pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation